Density functional theory studies on synthesis, chracterization and antibacterial activity of heteroaromatic substitution on 4n-thiosemicarbazone - Abdullah, Erna Normaya; Ahmad, Mohammad Norazmi; Omar, Muhammad Nor; Abdul Aziz, Yang Farina (2018)
Computational chemistry is rapidly emerging as an important sub-field of theoretical chemistry, where the primary focus is on solving chemically related problems by calculations. Density functional theory (DFT) is one of the fundamental theoretical methods based on quantum mechanics, and calculations using this theory will help researchers to obtain insight and also supporting data for better understanding of reaction mechanisms, chemical properties and energies of the title compound/product. The title project was proposed because, we want to study the effectiveness of combination between two bio-active fragments (drug) which are thiosemicarbazone and sulfonamide against antibacterial activity. However, we have to find the best method to synthesise the title compounds. Actually, the effectiveness and potential of the drug is related to their chemical properties and this will be studied using computational approach. So by using the DFT approach, the properties of each reactant in the synthesis of thiosemicarbazone will be identified and determined whether they act as a nucleophile or electrophile based on energy and electron distribution. After determining the reactivity properties of each reactant, the Fukui function method will be used to identify the atom that is involved in the reaction mechanism based on the electron density. The chemical properties of the new compounds will be evaluated based on chemical potential (μ), hardness (η), softness (s), electronegativity (χ) and electrophilic index (ω). Spectroscopic characterization, such as UV-vis, IR and NMR, will be compared between experiment and theory using DFT calculations. To study the potential of the drug (thiosemicarbazone) against the bacterial receptor protein, computational drug design will be used to clarify the mechanism of action of the protein–ligand complex. Finally, by using the theoretical and experimental approaches, we expect to produce new findings regarding the relationship between the chemical properties and biological activity for drug development in our nation.